2021
DOI: 10.1136/openhrt-2021-001638
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of coronary CT angiography in paroxysmal or first diagnosed atrial fibrillation

Abstract: ObjectivesThe presence of coronary artery disease (CAD) in patients hospitalised with paroxysmal or first diagnosed atrial fibrillation (AF) has major implications for antithrombotic therapy and cardiovascular event rate. Coronary CT angiography (CCTA) is a feasible tool to identify patients with concealed CAD. We aimed to evaluate the diagnostic role of early CCTA in patients hospitalised with paroxysmal or first diagnosed AF.MethodsIn a 5-year single-centre retrospective analysis, 566 patients with paroxysma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…A recent retrospective study showed that coronary CT angiography identified underlying coronary artery disease in 39% of individuals with paroxysmal of first-diagnosed AF. 18 In this context, coronary CT angiography is integrated in the diagnostic work-up of individuals with paroxysmal or first-diagnosed AF. 18 In addition, intensive strategies aiming to more efficient control of the atherosclerotic risk factors beyond OAC treatment, which could include lifestyle changes like smoking cessation, exercise and physical activity interventions, adoption of Mediterranean diet, and better weight control, as well as pharmaceutical interventions to control related comorbidities such as diabetes mellitus and dyslipidemia more efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study showed that coronary CT angiography identified underlying coronary artery disease in 39% of individuals with paroxysmal of first-diagnosed AF. 18 In this context, coronary CT angiography is integrated in the diagnostic work-up of individuals with paroxysmal or first-diagnosed AF. 18 In addition, intensive strategies aiming to more efficient control of the atherosclerotic risk factors beyond OAC treatment, which could include lifestyle changes like smoking cessation, exercise and physical activity interventions, adoption of Mediterranean diet, and better weight control, as well as pharmaceutical interventions to control related comorbidities such as diabetes mellitus and dyslipidemia more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In this context, coronary CT angiography is integrated in the diagnostic work-up of individuals with paroxysmal or first-diagnosed AF. 18 In addition, intensive strategies aiming to more efficient control of the atherosclerotic risk factors beyond OAC treatment, which could include lifestyle changes like smoking cessation, exercise and physical activity interventions, adoption of Mediterranean diet, and better weight control, as well as pharmaceutical interventions to control related comorbidities such as diabetes mellitus and dyslipidemia more efficiently. Accordingly, several retrospective studies showed that statin treatment in individuals with AF is associated with reduced risk for cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, Rottlander et al . conclude that there might be only a weak association between atrial fibrillation patients admitted to the hospital due to chest pain and relevant CAD [ 16 ]. Brown et al .…”
Section: Discussionmentioning
confidence: 99%
“…Besides male sex, age, diabetes, Framingham score and CHA 2 DS 2 -VASc score proved to be good predictors for CAD in a retrospective analysis of Rottlander et al . involving 566 paroxysmal or newly diagnosed atrial fibrillation patients [ 16 ]. However, according to Chen et al ., CACS was also observed without any conventional cardiovascular risk factors in 58% of the studied 324 patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…По результатам исследования у пациентов с пароксизмальной или впервые диагностированной ФП КТ-ангиография выявила ИБС (стеноз коронарной артерии ≥50%) в 39,2% случаев. Авторы рекомендуют интегрировать оценку кальцификации при КТ и КТ-ангиографии в диагностическое обследование пациентов с впервые возникшей или пароксизмальной ФП [50].…”
Section: принятые сокращенияunclassified